Polymorphism of the prolactin gene and its association with reproductive traits in F2 local crossed chickens - Ega Rosalinda; Heru Sasongko; Dyah Maharani (Veterinary World)
Background and Aim: Reproductive traits are crucial for genetic improvement in chickens. Prolactin (PRL) is a gene involved in a complex hormonal network that regulates reproduction in chickens. In this study, three local chicken breeds were crossed and had been produce a second filial (F2) generation, referred to as the F2 local crossed chicken. This study aimed to evaluate reproductive traits, identify single-nucleotide polymorphisms (SNPs), and assess genetic variation in the PRL gene of F2 local crossed chickens.